Accuracy of peripheral arterial tonometry in the diagnosis of obstructive sleep apnea - Pinto,José Antonio (2015)
ABSTRACT INTRODUCTION: The use of handheld devices that assess peripheral arterial tonometry has emerged as an auxiliary method for assessment and diagnosis of obstructive sleep apnea syndrome. OBJECTIVE: To evaluate the accuracy of peripheral arterial tonometry in the diagnosis of obstructive sleep apnea. METHODS: Contemporary cohort cross-sectional study. Thirty patients with suspected obstructive sleep apnea underwent peripheral arterial tonometry and assisted nocturnal polysomnography concomitantly. RESULTS: The mean apnea/hypopnea index by peripheral arterial tonometry was significantly higher than that by polysomnography (p < 0.001), but the values of both sleep studies were significantly correlated (r = 0.762). There was a high correlation between variables: minimum oxygen saturation (r = 0.842,p < 0.001), oxygen saturation < 90% (r = 0.799, p < 0.001), and mean heart rate (r = 0.951, p < 0.001). Sensitivity and specificity were 60% and 96.2% (AUC: 0.727;p = 0.113), respectively, when at a threshold value of 5 events/h. In severe cases (≥30 events/h), the result was a sensitivity of 77.8% and a specificity of 86.4% (AUC: 0.846, p = 0.003). CONCLUSION: Peripheral arterial tonometry is a useful portable device for the diagnosis of obstructive sleep apnea; its accuracy is higher in moderate and severe cases.